Terrorism and homeland security - White, Jonathan R. (Wadsworth / Cengage Learning, 2012)
Written by acclaimed national terrorism expert Jonathan R. White, the market-leading TERRORISM AND HOMELAND SECURITY, 7th Edition is widely recognized as the most comprehensive, balanced, and objective terrorism book on the market. White provides a theoretical and conceptual framework that enables readers to understand how terrorism arises and how it functions. Packed with cutting-edge coverage, the book discusses the most sophisticated theories by the best terrorist analysts in the world, while still focusing on the domestic and international threat of terrorism and the basic security issues surrounding terrorism today.